Dielectric investigations of polycrystalline samarium bismuth ferrite ceramic - Palaimiene, E. (2017)
Results of broadband dielectric investigations of samarium doped bismuth ferrite ceramics are presented in wide temperature range (20-800 K). At temperatures higher than 400 K, the dielectric properties of samarium bismuth ferrite ceramics are governed by Maxwell-Wagner relaxation and electrical conductivity. The DC conductivity increases and activation energy decreases with samarium concentration. In samarium doped bismuth ferrite, the ferroelectric phase transition temperature decreases with samarium concentration and finally no ferroelectric order is observed at x = 0.2. At lower temperatures, the dielectric properties of ferroelectric samarium doped bismuth ferrite are governed by ferroelectric domains dynamics. Ceramics with x = 0.2 exhibit the relaxor-like behaviour. (C) 2015 AIP Publishing LLC.